PEMBUATAN GAME RHYTHM “BEAT SPACE” DENGAN MENGGUNAKAN ALAT MIDI CONTROLLER PADA PLATFORM PC - Robert Matthew; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Beat Space is a PC platform based Rhythm game that uses MIDI Controller. The game is developed with Unity Game Engine and C# programming language for writing scripts in the game. It consists of 12 songs including the Indonesian traditional songs. The concept of the game is to gain points by pressing the buttons on the MIDI Controller device to hit the falling Notes that sync with the song rhythm. The score will be calculated from the number of notes that have been successfully pressed accurately. Testing in this game is carried out by the Blackbox testing method, Alpha testing by the supervisor, and Beta testing by distributing surveys to 31 respondents. The test results show that musical instruments in the form of a MIDI Controller can be used to play a game. This shows that the game "Beat Space" has unique controls and is quite entertaining.